The Integration of Nationalism and Religious Education at Islamic Elementary School in Lamongan, East Java - Habibah, Sulhatul; Marazi, Hamidullah; Wahyuddin, Imam; Junaidi, Mahbub; Sholikah, Khotimatus (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
In religious primary schools, nationalism education enhances students' patriotism. However, a common challenge in religious primary schools is the conflict between nationalist education and religious sectarianism. Achieving harmonious integration between nationalism and religious education can solve the problem. This study aims to comprehensively describe and analyze the integration strategy regarding nationalism and religious education employed at the Islamic Elementary School (SDI) Ar-Roudloh in Lamongan, East Java. This research, using a qualitative case study approach, reveals key findings: first, the integration of nationalism and religious education at Islamic Elementary Schools is manifested through a combined national and religious curriculum, including Independent, Cambridge, Tahfidh, and Qur'an curriculum; second, the success of this integration is facilitated by the active role of teachers both inside and outside the classroom in educating students; third, observations, interviews, and focus group discussions with teachers yield valuable insights into the integration model of nationalism and religious education. In summary, this research underscores the significance of a well-integrated curriculum to reinforce both nationalism and religious values among students effectively.